Haemorrhagic, proteolytic and neurotoxic activities produced by Duvernoy”™s gland secretion from the false coral snake (Erythrolamprus bizona Jan 1863) (Serpentes: Colubridae) - Lemoine, Karel; Rodríguez Acosta, Alexis (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Many colubrid snakes produce toxic oral secretions. Venom (DuvernoyÂ´s gland secretion) collected from Venezuelan species of opisthoglyphous (rear-fanged) colubrid snakes has been studied. Electrophoresis 20% SDS-PAGE were run to separate and characterize the different proteins present in secretion from the Duvernoy gland in Erythrolamprus bizona, the false coral snake under study. The venom displayed proteolytic (gelatinase) activity. To partially purify this proteolytic activity a chromatography ionic exchange mono Q2 column was used. To test haemorrhagic activity E. bizona DuvernoyÂ´s gland secretion on chicken embryos, mammalian (mice) skin and peritoneum were tested and haemorrhagic activity in both experiments was evident. Observing the symptoms of E. bizona DuvernoyÂ´s gland secretion in mice, it was seen to produce neurotoxic activity since several disorders associated with neurotoxins were observed. In conclusion, E. bizona DuvernoyÂ´s gland secretion showed proteolytic, haemorrhagic and neurotoxic activity. Â